Moving Forward From COVID-19: Bridging Knowledge Gaps in Maternal Health With a New Conceptual Model - Dickens, Molly J.; Pawluski, Jodi L.; Romero, L. Michael (Frontiers in Global Women's Health, 2020)
As the world faces the health crisis of a global pandemic — with healthcare protocols in overhaul, and patients and care teams experiencing unprecedented levels of stress and unpredictability — we predict that current knowledge gaps in maternal health will inevitably have a lasting impact on the health of women giving birth now and in the near future. Since we are decades away from closing the knowledge gaps we need filled today, we recommend shifting thinking towards a comprehensive conceptual model that merges knowledge of stress physiology, neurobiology, and pregnancy physiology. The model we present here, the Maternal Reactive Scope Model, is an expansion of the Reactive Scope Model built upon the concept of Homeostasis and Allostasis. The model provides a framework to consider pathways and interactions across physiological systems to attribute a physiological basis for considering stress exposure and bridge research gaps on mechanisms to measure or target for treatment. Our intention is to provide an adaptable, heuristic framework for discussion of research considerations and new healthcare models that aim to provide the best care for new mothers during and after the COVID-19 pandemic.